Progress in CRISPR Technology for Antiviral Treatments: Genome Editing as a Potential Cure for Chronic Viral Infections - Fatemeh Nouri; Farnaz Alibabaei; Behina Forouzanmehr; Hamed Tahmasebi; Valentyn Oksenych; Majid Eslami (Microbiology Research)
The CRISPR–Cas system has transformed molecular biology by providing precise tools for genome editing and pathogen detection. Originating from bacterial adaptive immunity, CRISPR technology identifies and cleaves genetic material from pathogens, thereby preventing infections. CRISPR–Cas9, the most widely utilized variant, creates double-stranded breaks in the target DNA, enabling genetic disruptions or edits. This approach has shown significant potential in antiviral therapies, addressing chronic infections, such as HIV, SARS-CoV-2, and hepatitis viruses. In HIV, CRISPR–Cas9 edits the essential viral genes and disrupts latent reservoirs, while CCR5 gene modifications render the T cells resistant to viral entry. Similarly, SARS-CoV-2 is targeted using CRISPR–Cas13d to inhibit the conserved viral genes, significantly reducing viral loads. Hepatitis B and C treatments leverage CRISPR technologies to target conserved genomic regions, limiting replication and expression. Emerging innovations, such as the PAC-MAN approach for influenza and base-editing systems to reduce off-target effects, further highlight the therapeutic versatility of CRISPR. Additionally, advances in Cas12a and Cas13 have driven the development of diagnostic platforms like DETECTR and SHERLOCK, which provide rapid and cost-effective viral detection. Innovative tools like AIOD-CRISPR enable accessible point-of-care diagnostics for early viral detection. Experimental approaches, such as targeting latent HSV-1 reservoirs, highlight the transformative potential of CRISPR in combating persistent infections.